Machine learning - Alpaydin, Ethem (Cambridge, Massachusetts The MIT Press, 2021)
An updated introduction for generalists to this powerful technology, its applications and possible future directions"-- Provided by publisher
Why we are interested in machine learning
Machine learning statistics, and data analytics
Pattern recognition
Neural networks and deep learning
Learning clusters and recommendations
Learning to take action
Challenges and risks
Where do we go from here?
Keywords: Machine learning. -- Artificial intelligence; Artificial Intelligence -- Machine Learning